If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -3 + 15 = 0 Reorder the terms: -3 + 15 + 9x = 0 Combine like terms: -3 + 15 = 12 12 + 9x = 0 Solving 12 + 9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 9x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 9x = 0 + -12 9x = 0 + -12 Combine like terms: 0 + -12 = -12 9x = -12 Divide each side by '9'. x = -1.333333333 Simplifying x = -1.333333333
| 3(2x-3)-5(x-2)= | | 2(x-6)=7(x+4) | | 10x-98/5=8x | | ay-4=dy-2 | | 14-3x+2= | | 4y-1=15y | | 6(w-2)=-48 | | -16=7(v-8)+3v | | t=4+4.91 | | -4x-3y=33 | | 38=2(u+7)+2u | | -x+8x-2p=0 | | 71-x=16+4x | | -(7z+3y-4x)= | | 4=Ts+4.91 | | (X-2)8=24 | | y-4=1/2(x-5) | | -8n-9=56 | | 9x-3x-6=6 | | 2x+8(x-2)=14 | | (5t^2-6t+7)+(8t-5)= | | 2(3x+2)=24 | | 3(x-5)+4x=5x-27 | | 7707=.34X | | 2+(-7b)=-23 | | X-5x-34=-10 | | 3(2x-4)=60 | | y=3/4(4-2) | | -2+(-7b)=-23 | | t=4s+4.9 | | 10(x+4)-3=14x+1 | | 4y^3-1=0 |